(untitled) (World Conference on Social Sciences, Law and Public Policy, 2026)
The adoption of the European Union Artificial Intelligence Act (Regulation 2024/1689) marks an unprecedented shift in the international regulation of artificial intelligence technologies, particularly regarding the extraterritorial application of copyright norms. Article 53 of this Regulation establishes obligations to comply with EU copyright law for providers of general-purpose AI models, regardless of where the training takes place, which creates fundamental challenges to the principles of international law and state sovereignty.